Energy Conversion and Storage Based on Hydrogen. State of art and Strategized Proposals in Mercosur - Martins, M. E.; Peretti, H. A.; Spinadel, E.; Zinola, C. F.; Visintin, A. (Rev. Téc. Fac. Ing. Univ. Zulia, 1970)
Renewable energies are a safe alternative to the socioeconomic problem that the Mercosur region is experiencing. Hydrogen is the ideal medium for wind and electric energy storage. Although hydrogen is the most abundant element in nature, it requires energy for its production, because it seldom occurs free. Pure hydrogen is obtained by water electrolysis. It is for that reason that in the Mercosur regions the ideal scenario that must be exploited is the combination of two elements, wind and hydrogen, inasmuch as the use of fuel cells allows obtaining steady electric energy in isolated places from wind energy, which is intermittent. Methods for obtaining hydrogen by the reforming of natural gas or biofuel with very good results are also being developed. Therefore, the present work focuses on both studies and research on hydrogen energy and its beneficial consequences in relation to renewable and non-renewable resources, and to the mitigation of the environmental impact during its use. The multidisciplinary character of this work has allowed approaching it from a basic and also technological aspect considering different possibilities, such as electricity generation in fuel cells and hydrogen production using wind energy, and their impact on the region.